Meta-Analysis Study: Effect of Means Ends Analysis (MEA) Model on Student's Mathematical Problem-Solving Skills - Sinta Purnamasari; Turmudi Turmudi; Dadang Juandi (Universitas Muhammadiyah Enrekang, 2023)
A comprehensive review of Means Ends Analysis (MEA) impact on mathematical problem-solving skills has not been studied extensively, As a result, few teachers are aware of the benefits that this approach has for children. This meta-analysis study was conducted to assess the overall impact of teaching students to solve mathematical problems using the MEA approach. Empirical information was obtained from URL links, Semantic Scholar, and Google Scholar. The search produced 18 articles that were written between 2009 and 2023. 18 items were eligible for analysis because they met the inclusion criteria. In the analysis tool, a random estimation model and Comprehensive Meta-Analysis (CMA) software are both utilized. The outcomes showed that the overall effect size of the study was 0.920. These results imply that the use of the MEA has a significant impact on students' mathematical problem-solving skills. After examining the moderator variables, it was found that the MEA model was successful when considering student sample sizes, but not when considering the educational level and demographics of the students. The application of MEA in enhancing students' mathematical problem-solving should be employed more frequently, particularly in elementary schools, according to this meta-analysis study's advice to Indonesian math teachers.